2015
DOI: 10.1655/herpetologica-d-13-00091
|View full text |Cite
|
Sign up to set email alerts
|

The Cellular Basis of Polymorphic Coloration in Common Side-Blotched Lizards,Uta stansburiana

Abstract: Diurnal lizards are useful model organisms for the study of color polymorphisms. The cellular basis of nonavian reptilian coloration and dermal chromatophores, as well as the different pigments contained therein, is relatively well understood. Nonetheless, specific predictions cannot be made for the biochemical chromatophore constituents of individual species a priori. Despite well-documented associations between throat coloration and behavioral, physiological, and life history traits, the cellular basis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 49 publications
(79 reference statements)
0
26
0
Order By: Relevance
“…Previous reports have described iridophores with randomly organized platelets in red and white skin of Phelsuma grandis where they produce broadband reflection [16]. In contrast, reflecting platelets in orange and yellow skin regions of Uta stansburiana [57], Sceloporus undulatus , and S. magister [56] are highly organized to reflect orange and yellow wavelengths. Even though broadband reflecting iridophores do not influence perceived colour, they may increase the brightness of colour regions and their overall conspicuousness to observers [3,103].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports have described iridophores with randomly organized platelets in red and white skin of Phelsuma grandis where they produce broadband reflection [16]. In contrast, reflecting platelets in orange and yellow skin regions of Uta stansburiana [57], Sceloporus undulatus , and S. magister [56] are highly organized to reflect orange and yellow wavelengths. Even though broadband reflecting iridophores do not influence perceived colour, they may increase the brightness of colour regions and their overall conspicuousness to observers [3,103].…”
Section: Discussionmentioning
confidence: 99%
“…4, 5). Unlike lizards [16,57,97] turtles lack a layer of dermal melanophores in the red-yellow skin regions. Turtles bask to thermoregulate and overheating may represent an immediate risk for them [129], but basking could also have a social function [130] for which it may be advantageous to accumulate heat at a slower rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, the costs of production or maintenance (i.e., honesty) of carotenoid-based ornaments have been studied in different organisms (in lizards, Fitze et al 2009 ; in birds, Mougeot et al 2009 ; in lizards, Cote et al 2010 ; in birds, Simons et al 2012 ). In addition to carotenoid-based ornaments, some yellow or orange-based coloration of lizards (especially American species) are instead based on pterins ( Weiss et al 2012 ; Haisten et al 2015 ). Thus, yellow ornaments based on pterines might be costly to produce because they are synthetized consuming purines via salvage pathways ( Morrison et al 1995 ; Weiss et al 2012 ).…”
mentioning
confidence: 99%
“…Melanophores play a key role in the contribution to the blue and UV-blue colorations ( Cox et al 2005 , 2008 ). In contrast, pigment-based colorations present a superficial layer of xantophores/erythrophores that can contain a combination of pigments (pterines and/or carotenoids) ( Kopena et al 2013 ; Olsson et al 2013 ; Haisten et al 2015 ) and that in combination with the remaining skin layers results in yellow, orange, or some red ornaments ( Grether et al 2004 ; San-Jose et al 2013 ). Experimental studies demonstrated the influence of hormones on the structural component ( San-Jose et al 2013 ) and the pigmentary component underlying the coloration of lizards ( Cox et al 2008 ; Cote et al 2010 ).…”
mentioning
confidence: 99%